1952
DOI: 10.1111/j.1440-1827.1952.tb00348.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Weight and Size of Internal Organs of Normal Japanese*

Abstract: As for the estimation of the weight and size of human internal organs many datas have already been published in Japan as well as in other foreign countries. The majority of them were based on the materials of pathological cases, and only a few were based on the materials of sudden deaths. Approximately 1800 autopsy cases are handled by the Medical Examiner Office of Tokyo-to yearly. Using these materials, we intended to determine the normal value of the weight and size of the internal organs of the Japanese. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0
2

Year Published

1985
1985
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 7 publications
2
14
0
2
Order By: Relevance
“…In other words, in the case of females, FLI was observed in the relatively hypertro phic thyroid glands, but not in the atrophic ones, although this is not the case in male thy roid glands. However, the average weight of thyroid glands with FLI over 70 years old females (17.4 ± 2.5 g) was almost compara ble to that (17.2 ± 0.65 g) of young Japanese females (21-25 years old) [Aimi et al, 1952], In the case of males, there was no significant difference in the weight of thyroid glands be tween elderly and young Japanese people, as well as between those with and without FLI. These findings were consistent with those of Zegarelli-Schmidt et al [1985], who exam ined 40 thyroid glands ranging in age between 16 and 90, and reported no significant age change in the weight.…”
Section: Discussionmentioning
confidence: 82%
“…In other words, in the case of females, FLI was observed in the relatively hypertro phic thyroid glands, but not in the atrophic ones, although this is not the case in male thy roid glands. However, the average weight of thyroid glands with FLI over 70 years old females (17.4 ± 2.5 g) was almost compara ble to that (17.2 ± 0.65 g) of young Japanese females (21-25 years old) [Aimi et al, 1952], In the case of males, there was no significant difference in the weight of thyroid glands be tween elderly and young Japanese people, as well as between those with and without FLI. These findings were consistent with those of Zegarelli-Schmidt et al [1985], who exam ined 40 thyroid glands ranging in age between 16 and 90, and reported no significant age change in the weight.…”
Section: Discussionmentioning
confidence: 82%
“…In a subsequent paper, Rasmussen [8] recorded the average weight of pituitary of 93 non-pregnant women between the ages of 16 and 84 years as 618.3 ± 94.2 mg and observed that the weight of the gland is more in older age group of 50-84 years (619.5 ± 103.4 mg) than in younger age group of 16-49 years (617.5 ± 88.5 mg). Aimi et al [11] weighed pituitary of 109 infants, 113 children and adolescents of both sexes of Japanese population. They found that although there was no consistency but, by and large, the weight of pituitary increased with age.…”
Section: Age Differences In Weightmentioning
confidence: 99%
“…According to Aimi et al (1952) and Tanaka et al (1989), there is a steep rise in brain weight during the first 5 years in both sexes with only slight increases thereafter. This was also noted with the present study.…”
Section: Discussionmentioning
confidence: 95%
“…The question of racial variation can only be effectively discussed if other factors which influence brain weight are considered, namely, body length and body weight of the newborn, gestational age, state of nourishment, cause of death, etc. Aimi et al (1952) weighed the brains of 64 male and 86 female Japanese neonates (0 day-one month) and noted average weights of 493.0 ± 12.5 gm in males and 498.2 ± 7.2 gm in females. However, Tanaka et al (1989) reported brain weights of 475.0 ± 102.3 gm in male and 467.5 ± 124.8 gm in female Japanese neonates.…”
Section: Discussionmentioning
confidence: 99%